G-C3N4 / vat yellow GCN composite photocatalyst and preparation method thereof
By preparing g-C3N4/reduced yellow GCN composite photocatalyst, the problems of low dye wastewater treatment efficiency and low g-C3N4 photocatalytic efficiency in the prior art were solved, and efficient degradation of methyl orange and rhodamine B was achieved. And maintain good photocatalytic stability.
Patent Information
- Application Number
- CN202411372733.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-10
AI Technical Summary
The prior art has problems of difficulty in handling dye wastewater and low efficiency, and g-C3N4, as a photocatalytic material, has problems of small specific surface area and low photocatalytic efficiency.
Using the preparation method of g-C3N4/reduced yellow GCN composite photocatalyst, reducing yellow GCN is reacted with NaOH solution and sodium disulfite, and then stirred with H2O2, centrifuged, washed and dried to obtain reduced yellow GCN nano powder, and then with melamine The pyrolysis reaction was carried out and the g-C3N4 powder was grinded, and then hydrothermal reaction was carried out with deionized water to obtain a g-C3N4/reduced yellow GCN composite photocatalyst.
Improve the photocatalytic performance of reducing yellow GCN, achieve efficient degradation of methyl orange and rhodamine B, with degradation rates of 81% and 100% respectively, and maintain good photocatalytic stability. After three use, there are still good ones. Degradation effect.
Smart Images

Figure CN119281362A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photocatalysts, and specifically relates to a g-C3N4 / reduced yellow GCN composite photocatalyst and a preparation method thereof. Background Art
[0002] Reduced Yellow GCN, Reduced Green Copper Nitrate, is a bright yellow with a bright color. It is used as a reducing dye in the printing and dyeing industry. At the same time, Reduced Yellow GCN belongs to anthraquinone compounds and also has good light absorption and conductivity properties.
[0003] g-C3N4 is considered to be an excellent photocatalytic material and a new type of two-dimensional nano inorganic semiconductor photocatalyst. It has stable physical and chemical properties and good light response, so it has attracted widespread attention. The main elements are C and N. C atoms and N atoms have sp 2 Hybridization forms conjugated π bonds. Under visible light irradiation, g-C3N4 has the properties of photocatalytic pollution degradation, photocatalytic water splitting to produce hydrogen, photocatalytic organic synthesis and photocatalytic carbon dioxide reduction, and is widely used in the field of photocatalytic explanation. At the same time, g-C3N4 has many disadvantages, such as small specific surface area, high recombination rate of photogenerated electron-hole pairs, and low photocatalytic efficiency.
[0004] The problem of dye wastewater treatment is becoming increasingly serious. Common dye wastewater treatment methods include adsorption, chemical oxidation, membrane separation, etc. These methods can solve the dye wastewater problem to a certain extent, but they also have disadvantages such as difficult operation and low efficiency. It is of great significance to seek more efficient dye wastewater treatment technology. Summary of the invention
[0005] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0006] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.
[0007] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a g-C3N4 / reduced yellow GCN composite photocatalyst.
[0008] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0009] Reduced yellow GCN is added to NaOH solution, and then sodium dithionite and thiourea dioxide are added to react to obtain solution Ⅰ;
[0010] Solution I was added with H2O2, and the mixture was stirred, centrifuged, washed, and dried to obtain reduced yellow GCN nanopowder;
[0011] The melamine was thermally decomposed and ground to obtain g-C3N4 powder;
[0012] The g-C3N4 powder and reduced yellow GCN nanopowder are dispersed in deionized water, subjected to hydrothermal reaction, and then cooled, washed, centrifuged and dried in sequence to obtain a g-C3N4 / reduced yellow GCN composite photocatalyst.
[0013] As a preferred scheme of the preparation method of the g-C3N4 / reduced yellow GCN composite photocatalyst described in the present invention, the mass ratio of the reduced yellow GCN, NaOH and sodium dithionite is 2:2.25 to 3:3.
[0014] As a preferred embodiment of the method for preparing the g-C3N4 / reduced yellow GCN composite photocatalyst of the present invention, the mass of the reduced yellow GCN is 3 to 9 g.
[0015] As a preferred embodiment of the method for preparing the g-C3N4 / reduced yellow GCN composite photocatalyst of the present invention, the reaction temperature is 70-75°C.
[0016] As a preferred scheme of the preparation method of the g-C3N4 / reduced yellow GCN composite photocatalyst described in the present invention, the reaction time is 15 to 20 minutes.
[0017] As a preferred scheme for the preparation method of the g-C3N4 / reduced yellow GCN composite photocatalyst described in the present invention, the volume ratio of the H2O2 to the solution I is 1:37.5-40.
[0018] As a preferred scheme of the preparation method of the g-C3N4 / reduced yellow GCN composite photocatalyst described in the present invention, the mass ratio of the g-C3N4 and reduced yellow GCN nanopowder is 1:0.25-8.
[0019] As a preferred scheme for the preparation method of the g-C3N4 / reduced yellow GCN composite photocatalyst described in the present invention, the heating rate of the pyrolysis reaction is 5-6°C / min, and when the temperature rises to 700-750°C, heating is continued for 4-5h.
[0020] As a preferred embodiment of the method for preparing the g-C3N4 / reduced yellow GCN composite photocatalyst of the present invention, the temperature of the hydrothermal reaction is 160-180°C and the time is 12-24 hours.
[0021] Another object of the present invention is to overcome the shortcomings of the prior art and provide a g-C3N4 / reduced yellow GCN composite photocatalyst prepared by the preparation method of the g-C3N4 / reduced yellow GCN composite photocatalyst, wherein: the g-C3N4 / reduced yellow GCN composite photocatalyst has a degradation rate of 81% for methyl orange and a degradation rate of 100% for rhodamine B. After being used three times, it still has a good degradation effect on methyl orange, and the degradation rate is higher than 80%.
[0022] Beneficial effects of the present invention:
[0023] (1) The g-C3N4 prepared by the present invention improves the photocatalytic performance of reduced yellow GCN, and achieves efficient degradation of methyl orange and rhodamine B by optimizing the ratio of g-C3N4 to reduced yellow GCN, with the degradation rate of methyl orange reaching 81% and the degradation rate of rhodamine B approaching 100%.
[0024] (2) The g-C3N4 / reduced yellow GCN composite photocatalyst of the present invention has good photocatalytic stability and still has a good degradation effect on methyl orange after being used three times, with a degradation rate of more than 80%.
[0025] (3) Through the comparative experiment of the effect of different scavengers on the photodegradation rate, the degradation mechanism of methyl orange by g-C3N4 / reduced yellow GCN composite photocatalyst was explored. The active groups involved in the degradation of methyl orange by g-C3N4 / reduced yellow GCN composite photocatalyst are mainly ·O2 - . BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:
[0027] Figure 1 This is the XRD diagram of g-C3N4, reduced yellow GCN nanopowder and g-C3N4 / GCN composite photocatalyst in embodiment 1 of the present invention.
[0028] Figure 2 This is the SEM picture of g-C3N4, reduced yellow GCN nano powder and g-C3N4 / reduced yellow GCN composite photocatalyst in embodiment 1 of the present invention.
[0029] Figure 3 This is a transient photocurrent response curve diagram of g-C3N4, reduced yellow GCN nanopowder and g-C3N4 / reduced yellow GCN composite photocatalyst under simulated ultraviolet visible light in Example 1 of the present invention.
[0030] Figure 4 This is a Mott-Schottky curve diagram of reduced yellow GCN, reduced yellow GCN nanopowder, g-C3N4 and g-C3N4 / reduced yellow GCN composite photocatalyst in Example 1 of the present invention.
[0031] Figure 5 This is a diagram simulating the photocatalytic cyclic degradation rate of MO solution by g-C3N4 / reduced yellow GCN composite photocatalyst under ultraviolet-visible light.
[0032] Figure 6 This is a diagram of the photocatalytic degradation of methyl orange solution by the composite photocatalysts with different g-C3N4 / reduced yellow GCN ratios in Example 1 and Example 2 of the present invention under simulated ultraviolet visible light.
[0033] Figure 7 This is a graph showing the photodegradation rate of methyl orange solution by the g-C3N4 / reduced yellow GCN composite photocatalyst under simulated ultraviolet visible light in Example 3 of the present invention with different capture agents.
[0034] Figure 8 This is a diagram showing the degradation effect of Rhodamine B by g-C3N4 / reduced yellow GCN in Example 4 of the present invention. DETAILED DESCRIPTION
[0035] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0036] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0037] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0038] The specific steps of the photocatalytic degradation experiment in the present invention are:
[0039] Weigh 0.1g of the photocatalyst and pour it into a 250mL beaker. Add 100mL of methyl orange (MO) solution with a concentration of 10mg / L as a simulated pollutant. Place the beaker in a magnetic stirring device to ensure that the catalyst and pollutant solutions are fully mixed. Stir evenly in the dark at room temperature of 25℃ for 30min to simulate the light-shielding adsorption process. After 30min, take out 5mL of the reaction solution. Centrifuge using a micro high-speed desktop centrifuge to separate the solid catalyst and the solution. Aspirate the clarified solution and measure its absorbance value on a UV-visible spectrophotometer;
[0040] After the light-shielding adsorption experiment is completed, it is considered that the suspension solution has reached the adsorption-desorption equilibrium state. Turn on the xenon light source to simulate the visible light irradiation conditions. Carry out the photocatalytic degradation experiment under visible light irradiation, and take out 5mL of the reaction solution every 10min until the reaction is carried out for 1h. Centrifuge the suspension taken out each time with a micro high-speed desktop centrifuge to obtain a clear solution. Use a UV-visible spectrophotometer to measure the absorbance value of the clear solution at the maximum absorption wavelength of the pollutant to be degraded.
[0041] The specific steps of the active group capture experiment in the present invention are:
[0042] In a 250mL beaker, add 0.1g of composite photocatalyst and 100mL of 10mg / L methyl orange (MO) solution, then add 1mL of p-benzoquinone solution, EDTA-2Na solution and isopropanol solution respectively, then stir magnetically for 30min in a dark place, then irradiate under simulated ultraviolet visible light and simulated visible light, take the solution after every 10min interval, for a total of 1h, centrifuge, take the supernatant to test the absorbance and analyze;
[0043] 0.1g of sample was added to 100mL MO solution with a concentration of 10mg / L, and then stirred for 30min under light shielding to achieve adsorption and desorption equilibrium. The sample was irradiated with a 300W xenon lamp (i.e., simulated ultraviolet lamp) for 60min, and the liquid was collected every 10min, then centrifuged, the upper layer of liquid was drawn, and the absorbance was measured. Finally, the photodecomposition rate of the sample to the liquid was calculated according to formula (1);
[0044]
[0045] Where: η—photodegradation rate, %;
[0046] A0—absorbance of MO solution without illumination;
[0047] A t —The absorbance of MO solution at t.
[0048] According to formula (2), the Langmuir-Hinshelwood pseudo-first-order reaction kinetic model was used to study the photocatalytic degradation rate of the sample to MO aqueous solution. t The ratio of A0 to A t .
[0049]
[0050] Where: K—photodegradation rate, / min;
[0051] C0—the concentration of MO solution without light exposure, mg / L;
[0052] C t —Concentration of MO solution at illumination time t, mg / L.
[0053] Example 1
[0054] This embodiment provides a method for preparing a g-C3N4 / reduced yellow GCN composite photocatalyst, specifically:
[0055] Pour 150mL of distilled water into a 250mL distillation flask, add 6.75g of NaOH, place the flask on a magnetic stirrer and stir for 5 minutes to dissolve the NaOH lumps. After the NaOH is completely dissolved, add 6g of reduced yellow GCN, stir for 5 minutes, and add 9g of sodium dithionite and 2.5g of thiourea dioxide. Place the distillation flask in an oil bath and stir to heat the solvent evenly. Set the oil bath temperature to 70°C and time it for 15 minutes.
[0056] The solvent was poured into a 500 mL beaker, 4 mL of H2O2 was added, the volume ratio of H2O2 to the solution I was 1:37.5, a magnetic stirrer was used for 24 hours, and the vat yellow GCN nanopowder was obtained by centrifugation, washing and drying.
[0057] Weigh 10 g of melamine and put it into a ceramic crucible with a lid. Place the ceramic crucible containing melamine in a muffle furnace, set the heating rate of the muffle furnace to 5°C / min, and when the temperature rises to 700°C, continue heating for 4 hours to carry out pyrolysis reaction.
[0058] After the pyrolysis reaction is completed, it is cooled naturally to room temperature. When the sample cools to room temperature, the solid product inside is taken out. The solid product is ground into powder using a mortar and pestle to ensure that the particle size of g-C3N4 is uniform.
[0059] Weigh 0.5 g of g-C3N4 and 0.25 g of reduced yellow GCN nanopowder and pour them into a beaker containing 100 mL of deionized water. Place the beaker in an ultrasonic cleaner and ultrasonicate for 30 min.
[0060] The uniformly dispersed suspension was poured into a 150 mL polytetrafluoroethylene-lined autoclave, which was placed in an oven for hydrothermal reaction at 180° C. for 12 hours.
[0061] After the reaction is completed, the reactor is taken out and cooled to room temperature, and the reaction product is washed with deionized water for multiple times to remove unreacted substances and impurities. The product is centrifuged and dried to obtain a g-C3N4 / reduced yellow GCN composite photocatalyst powder.
[0062] Figure 1 The XRD spectra of g-C3N4, reduced yellow GCN nanopowder and g-C3N4 / reduced yellow GCN composite photocatalyst in this embodiment. It can be seen that the diffraction peak near 13.0° represents the (100) plane. This peak is related to the distance of the repeating units in the conjugated layer plane of g-C3N4, and specifically corresponds to the macrocyclic structure between tri-s-triazine units. Tri-s-triazine is a basic structural unit in g-C3N4; the other diffraction peak near 27.3° belongs to the (002) plane, representing a typical graphite layered structure, corresponding to the interlayer stacking of aromatic hydrocarbons, indicating that g-C3N4 has a layered structure similar to graphite. When reduced yellow GCN is compounded with g-C3N4 to form a g-C3N4 / reduced yellow GCN composite photocatalyst, the characteristic diffraction peak intensity of the (002) plane gradually decreases. The addition of reduced yellow GCN destroys the original graphite layered structure or changes its stacking method to some extent. Although the intensity of the diffraction peak of the (002) plane decreases, the composite photocatalyst still retains a diffraction peak at about 21.7°, indicating that the g-C3N4 / reduced yellow GCN composite photocatalyst still maintains a graphene-like structure with graphite crystallites. Electrons can move more easily in this layered structure, which is conducive to the transfer of photogenerated electrons and promotes the absorption and utilization efficiency of light energy by the catalyst. Therefore, the graphene-like structure of the g-C3N4 / reduced yellow GCN composite photocatalyst can greatly promote the progress of the photocatalytic reaction.
[0063] Figure 2The SEM images of g-C3N4, reduced yellow GCN nanopowder and g-C3N4 / reduced yellow GCN composite photocatalyst are shown in Figure 1, where (a) g-C3N4×1,600, (b) g-C3N4×4,000, (c) reduced yellow GCN nanopowder×10,000, (d) reduced yellow GCN nanopowder×60,000, (e) g-C3N4 / reduced yellow GCN composite photocatalyst×2,000, and (f) g-C3N4 / reduced yellow GCN composite photocatalyst×30,000. It can be seen that the single g-C3N4 material is easy to agglomerate to form a dense structure, and the layered structure is relatively small, which limits its specific surface area and reactive sites. The reduced yellow GCN nanopowder obtained after pyrolysis has a loose structure and is in the form of nanosheets. The loose nanosheet structure helps to increase the specific surface area of the material and provide more reactive sites. Compared with single g-C3N4, the surface of the g-C3N4 / reduced yellow GCN composite photocatalyst modified with reduced yellow GCN becomes loose, forming a hydrangea-like structure, making the catalyst surface rougher and more fragmented. The loose, rough and fragmented surface is conducive to increasing the specific surface area of the material, providing more reactive sites, thereby increasing the possibility of contact with organic pollutants, and facilitating the interaction between the composite photocatalyst and pollutants during adsorption and degradation, thereby improving the photocatalytic performance of the catalyst.
[0064] Figure 3 The transient photocurrent response curves of reduced yellow GCN nanopowder, g-C3N4 and g-C3N4 / reduced yellow GCN composite photocatalyst under simulated ultraviolet visible light irradiation. It can be seen that in a dark environment, g-C3N4, reduced yellow GCN nanopowder and g-C3N4 / reduced yellow GCN composite photocatalyst almost do not generate photocurrent. As the light is injected, the photocurrent responds accordingly. Among them, the magnitude of the photocurrent intensity is g-C3N4 / reduced yellow GCN composite photocatalyst>reduced yellow GCN nanopowder>g-C3N4. The photocurrent is caused by the photogenerated electrons in the catalyst. The higher the photocurrent intensity, the higher the separation efficiency of the photogenerated carriers and the better the photocatalytic performance. The photocurrent of the composite g-C3N4 / reduced yellow GCN composite photocatalyst obtained by compounding is significantly stronger than that of g-C3N4 and reduced yellow GCN nanopowder, further proving that the g-C3N4 / reduced yellow GCN composite photocatalyst has better photocatalytic performance.
[0065] Figure 4The Mott-Schottky curves of reduced yellow GCN, reduced yellow GCN nanopowder, g-C3N4 and g-C3N4 / reduced yellow GCN composite photocatalyst. It can be seen that the type of semiconductor photocatalyst can be determined by the Mott-Schottky test. When the slope of the tangent line of the curve is positive, the catalyst is an n-type semiconductor. When the slope of the tangent line of the curve is negative, the catalyst is a p-type semiconductor. The slopes of the Mott-Schottky curves of reduced yellow GCN, reduced yellow GCN nanopowder, g-C3N4 and g-C3N4 / reduced yellow GCN composite photocatalyst are positive, proving that they are n-type semiconductors.
[0066] Figure 5 The photocatalytic degradation diagram of the g-C3N4 / reduced yellow GCN composite photocatalyst is shown in Figure 2. It can be seen that under UV-visible light irradiation, after three repeated experiments, the photocatalytic degradation of the g-C3N4 / reduced yellow GCN composite photocatalyst (1:0.5) has hardly changed, proving that the prepared g-C3N4 / reduced yellow GCN composite photocatalyst has good photocatalytic stability.
[0067] Example 2
[0068] The difference between this embodiment and embodiment 1 is that the mass ratio of g-C3N4 to reduced yellow GCN is adjusted to 1:0.25, 1:1, 1:2, 1:4, and 1:8, and the other steps are the same as those in embodiment 1 to prepare g-C3N4 / reduced yellow GCN composite photocatalysts with different mass ratios.
[0069] Figure 6 (a) and (b) are the photocatalytic degradation curves and pseudo first-order kinetic curves of methyl orange under simulated UV-visible light irradiation of different photocatalysts. Figure 6 As can be seen from (a), the g-C3N4 / reduced yellow GCN composite photocatalyst has a good photocatalytic effect, and the photocatalytic efficiency is significantly better than that of reduced yellow GCN nanopowder and g-C3N4. Among them, the g-C3N4 / reduced yellow GCN mass ratio is 1:0.5, and the photocatalytic effect is the best, which can degrade more than 81% of methyl orange in 1 hour. Figure 6 (b) It can be seen that the pseudo-first-order rate constant K of the g-C3N4 / reduced yellow GCN composite photocatalyst (1:0.5) is the largest, which is 0.02586 min -1 Compared with the single photocatalyst g-C3N4 and reduced yellow GCN nanopowder, it exhibits a higher photocatalytic effect and has better photocatalytic efficiency.
[0070] Example 3
[0071] This example compares the effects of different capture agents (isopropanol, p-benzoquinone, disodium ethylenediaminetetraacetate) on the photodegradation rate of the g-C3N4 / reduced yellow GCN composite photocatalyst in Example 1. Figure 7Isopropyl alcohol (IPA), p-benzoquinone (p-BQ), and disodium ethylenediaminetetraacetate (EDTA-2Na), among which IPA can capture ·OH, and p-BQ can capture ·O2 - EDTA-2Na can capture h + . When p-BQ is added to capture O2 - After adding EDTA-2Na capture h + After adding IPA to capture ·OH, the degradation rate of MO was 72.71%. After adding IPA to capture ·OH, the degradation rate of MO was 74.71%. This shows that the active radical involved in the degradation of methyl orange by g-C3N4 / reduced yellow GCN composite photocatalyst is mainly ·O2 - .
[0072] Example 4
[0073] In this example, the g-C3N4 / reduced yellow GCN composite photocatalyst in Example 1 was used to photocatalytically degrade rhodamine B. The photocatalytic degradation experimental operation was the same as that of methyl orange. The degradation effect was as follows: Figure 8 As shown, it can be seen that Rhodamine B was completely degraded after 5 min.
[0074] Comparative Example 1
[0075] The difference between this comparative example and Example 1 is that the compounding ratio of g-C3N4 and GCN is adjusted to 0.2:1, and the other steps are the same as Example 1, and the doping fails.
[0076] In summary, g-C3N4 in the present invention improves the photocatalytic performance of reduced yellow GCN, and achieves efficient degradation of methyl orange and rhodamine B by optimizing the ratio of g-C3N4 and reduced yellow GCN, with a degradation rate of 81% for methyl orange and nearly 100% for rhodamine B; the composite photocatalyst of the present invention has good photocatalytic stability, and after three uses, it still has a good degradation effect on methyl orange, with a degradation rate of more than 80%. The active groups involved in the degradation of methyl orange by the g-C3N4 / reduced yellow GCN composite photocatalyst are mainly ·O2 - .
[0077] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. A method for preparing a g-C3N4 / reduced yellow GCN composite photocatalyst, characterized in that: include, Reduced yellow GCN is added to NaOH solution, and then sodium dithionite and thiourea dioxide are added to react to obtain solution Ⅰ; Solution I was added with H2O2, and the mixture was stirred, centrifuged, washed, and dried to obtain reduced yellow GCN nanopowder; The melamine was thermally decomposed and ground to obtain g-C3N4 powder; The g-C3N4 powder and reduced yellow GCN nanopowder are dispersed in deionized water, subjected to hydrothermal reaction, and then cooled, washed, centrifuged and dried in sequence to obtain a g-C3N4 / reduced yellow GCN composite photocatalyst.
2. The method for preparing the g-C3N4 / reduced yellow GCN composite photocatalyst according to claim 1, characterized in that: The mass ratio of the vat yellow GCN, NaOH and sodium dithionite is 2:2.25 to 3:
3.
3. The method for preparing the g-C3N4 / reduced yellow GCN composite photocatalyst according to claim 2, characterized in that: The mass of the vat yellow GCN is 3-9 g.
4. The method for preparing the g-C3N4 / reduced yellow GCN composite photocatalyst according to claim 1, characterized in that: The reaction temperature is 70-75°C.
5. The method for preparing the g-C3N4 / reduced yellow GCN composite photocatalyst according to claim 4, characterized in that: The reaction time is 15 to 20 minutes.
6. The method for preparing the g-C3N4 / reduced yellow GCN composite photocatalyst according to claim 1, characterized in that: The volume ratio of the H2O2 to the solution I is 1:37.5-40.
7. The method for preparing the g-C3N4 / reduced yellow GCN composite photocatalyst according to claim 1, characterized in that: The mass ratio of the g-C3N4 to the reduced yellow GCN nano powder is 1:0.25-8.
8. The method for preparing the g-C3N4 / reduced yellow GCN composite photocatalyst according to claim 1, characterized in that: The heating rate of the pyrolysis reaction is 5-6°C / min. When the temperature rises to 700-750°C, heating is continued for 4-5h.
9. The method for preparing the g-C3N4 / reduced yellow GCN composite photocatalyst according to claim 1, characterized in that: The temperature of the hydrothermal reaction is 160-180° C. and the time is 12-24 hours.
10. The g-C3N4 / reduced yellow GCN composite photocatalyst prepared by the preparation method of the g-C3N4 / reduced yellow GCN composite photocatalyst according to any one of claims 1 to 9, characterized in that: The g-C3N4 / reduced yellow GCN composite photocatalyst has a degradation rate of 81% for methyl orange and a degradation rate of 100% for rhodamine B. After being used three times, it still has a good degradation effect on methyl orange, with a degradation rate higher than 80%.